Pengembangan Kegiatan Pembiasaan Pelajar Pancasila dalam Membentuk Akhlak yang Mulia di TK PKK 01 Sengonagung - Achmad Yusuf; Istifadah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
i1Thie 1aiim ofi 1tihis 1reisearch 1iis 1toi 1pirovide proivisions 1fori 1piarents1, i i1teachers i1and ichildren i1to i1understand i1the i1moral idevelopment i1of i1preschool i1children ibefore i1entering ii1elementary iii1school1i. i1The idevelopment i1of i1activities i1to i11111shape i1miorialis i1iis i1reialily ineiedied i1biy i1cihiildiren i1today1i, 1in i1this i1case i1teachers i1and iparents i1play i1a very i1important 1role 1in 1strengthening 1the 1development 1of 1activities to 1shape 1morals 1for 1students 1by modeling 1what 1is 1taught 1and imitated 1by 1students1. 1This 1research uses 1the 1participatory 1action 1research 1 (1PAR1) 1method, 1data 1collection 1techniques 1in 111this 1research 1are 1interviews, 1observation 1and 1documentation. 1The 1results of 1this 1research 1show 1that children 1at 1Kindergarten PKK 101 1SENGONAGUNG still 1have 1deficiencies in 1children's 1moral 1development, 1children do 1not 1understand and 1differentiate 1between good 1and 1bad1, and 1parents' 1parenting patterns 1in developing 1moral education 1or 1activities 1are 1not fully 1understood1. This 1shows that 1parents and 1teachers must 1work 1together to 1develop 1children's moral 1formation 1in 1the 111family 1and 1community 1environment. 1This 1journal explains 1material 1and 1activities for 1forming children's 1morals1. Therefore1, 1it can 11be 1concluded that 1this 1research 1is suitable 1for 1equipping 1parents and 1teachers 1at 1Kindergarten PKK 101 1SENGONAGUNG 1with knowledge 1about 1the 1activities of 1parents1, teachers 1and 1children to 1prepare 1preschool children 1with 1noble morals1. 1